Perioperative challenges in managing a patient with COVID-19 undergoing debridement for massive scalp myiasis - Lo, Shiu Yin; Teah, Ming Kai; Ho, Yan Zheng; Yeap, Boon Tat (BMJ Publishing Group Limited, 2021)
A young man presented to our centre needing an urgent debridement of his postcraniotomy wound due to massive myiasis during the COVID-19 pandemic in October 2020. Prior to the surgery, his nasopharyngeal swab real-time PCR test result was unknown. One day later, it returned as SARS-CoV-2 positive. All healthcare workers who were involved in the patient management avoided cross infection as they wore appropriate personal protective equipment. This article depicts the importance of adequate preparations when handling potentially infectious patients and the perioperative issues associated with it.